Updates on mesenchymal stem cell therapies for articular cartilage regeneration in large animal models - Liu, Timothy P.; Ha, Pin; Xiao, Crystal Y.; Kim, Sang Yub; Jensen, Andrew R.; Easley, Jeremiah; Yao, Qingqiang; Zhang, Xinli (Frontiers in Cell and Developmental Biology, 2022)
There is an unmet need for novel and efficacious therapeutics for regenerating injured articular cartilage in progressive osteoarthritis (OA) and/or trauma. Mesenchymal stem cells (MSCs) are particularly promising for their chondrogenic differentiation, local healing environment modulation, and tissue- and organism-specific activity; however, despite early in vivo success, MSCs require further investigation in highly-translatable models prior to disseminated clinical usage. Large animal models, such as canine, porcine, ruminant, and equine models, are particularly valuable for studying allogenic and xenogenic human MSCs in a human-like osteochondral microenvironment, and thus play a critical role in identifying promising approaches for subsequent clinical investigation. In this mini-review, we focus on [1] considerations for MSC-harnessing studies in each large animal model, [2] source tissues and organisms of MSCs for large animal studies, and [3] tissue engineering strategies for optimizing MSC-based cartilage regeneration in large animal models, with a focus on research published within the last five years. We also highlight the dearth of standard assessments and protocols regarding several crucial aspects of MSC-harnessing cartilage regeneration in large animal models, and call for further research to maximize the translatability of future MSC findings.